Analisis Sistem Monitoring Pendidikan Anak Usia Dini Metode Prototipe pada TKS IT Al Azhar OKI - Monika Sima; Tata Sutabri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Education is used as a means of improving human resources. In increasing educational progress, a data management system is needed such as student, class, educator and education data, as well as recapitulation of school data reports for early childhood education levels. This Early Childhood Monitoring Information System was built for the process of monitoring Early Kindergarten (TK) reports to control student activities at school and make it easier to provide information on the development of children's activities that are reported in student activities, without having to use the old system by recording all student progress. manually because it is less efficient in its use and makes it easier for teachers to monitor students. The method used in system development is prototyping. The use of information systems makes it easier for teachers to input monitoring data and results of grades so that teacher users can easily monitor the progress of their students.